2018
DOI: 10.1111/1462-2920.14280
|View full text |Cite
|
Sign up to set email alerts
|

Elemental sulfur reduction in the deep‐sea vent thermophile, Thermovibrio ammonificans

Abstract: The reduction of elemental sulfur is an important energy-conserving pathway in prokaryotes inhabiting geothermal environments, where sulfur respiration contributes to sulfur biogeochemical cycling. Despite this, the pathways through which elemental sulfur is reduced to hydrogen sulfide remain unclear in most microorganisms. We integrated growth experiments using Thermovibrio ammonificans, a deep-sea vent thermophile that conserves energy from the oxidation of hydrogen and reduction of both nitrate and elementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 74 publications
1
16
0
Order By: Relevance
“…All of these sulfur-reducing archaea lack a conventional sulfur reduction pathway. Therefore, we hypothesize that in elemental-sulfur/polysulfiderich environments, SQR-like proteins might catalyze the reduction of elemental sulfur/ polysulfide to H 2 S. A similar hypothesis has been proposed in a deep-sea thermophile, Thermovibrio ammonificans, after detection of the overexpression of SQR-like genes during sulfur respiration (68). While SQR-like proteins have not been shown to reversibly catalyze sulfide oxidation/reduction yet, there are precedents for reversible enzymes.…”
Section: Discussionsupporting
confidence: 55%
“…All of these sulfur-reducing archaea lack a conventional sulfur reduction pathway. Therefore, we hypothesize that in elemental-sulfur/polysulfiderich environments, SQR-like proteins might catalyze the reduction of elemental sulfur/ polysulfide to H 2 S. A similar hypothesis has been proposed in a deep-sea thermophile, Thermovibrio ammonificans, after detection of the overexpression of SQR-like genes during sulfur respiration (68). While SQR-like proteins have not been shown to reversibly catalyze sulfide oxidation/reduction yet, there are precedents for reversible enzymes.…”
Section: Discussionsupporting
confidence: 55%
“…recently also proposed a cytoplasmatic sulfur reduction mediated by an NSR‐like protein in a deep‐sea vent thermophile, Thermovibrio ammonificans , based on transcriptomic and proteomic analyses (Jelen et al ., 2018). T. ammonificans grows chemolithoautotrophically at optimal temperature of 75 °C and forms a deep branch within the phylum Aquificae (Jelen et al ., 2018). Prior to our study, cytoplasmic sulfur reduction was only reported in A. aeolicus and T. ammonificans , both of which are deep‐branched in bacterial phylogenetic tree and hyperthermophilic.…”
Section: Discussionmentioning
confidence: 99%
“…Sulfate is highly abundant on the current earth. Hence, sulfate reduction dominates reductive processes in the global sulfur cycle, although the reduction and disproportionation of the intermediate sulfur species, e.g., sulfur ( 7 , 8 ), sulfite ( 8 ), thiosulfate, and tetrathionate ( 9 , 10 ), could be significant in localized settings.…”
Section: Introductionmentioning
confidence: 99%